Analysis of Aqiqah Business Marketing in Aqiqah Farm Medan Farm Sunggal District Medan City - Dedi Rambe; Armyn Hakim Daulay; Fuad Hasan; Muheri Indra Aja (Jurnal Peternakan Integratif, 2024)
Ruminants are an important source of protein for humans which also provides economic benefits. This study aims to determine the general description of Aqiqah Medan Farm, marketing mix, income value, R/C ratio, and B/C ratio. Study method uses quantitative descriptive analysis with puIDRosive sample selection. The parameters observed were marketing mix, income, R/C ratio and B/C ratio. The results of the study were products sold in the form of live sheep and processed dishes, with the lowest selling price on live livestock of IDR.850,000/head, and processed dishes of IDR.1,450,000/head. The revenue earned was IDR.60,676,250/month, with an R/C ratio and B/C ratio value of 2.26, and 1.26, respectively. In conclusion that Aqiqah Medan Farm business is considered feasible.